Development of Coffee Fruit Skin (Coffea canephora) formula as Antioxidant peel-off Masks. - Fith Khaira Nursal; Anisa Amalia; Nining Nining; Dania Athaya Putri; Kinanti Dara Larasati (JSFK (Jurnal Sains Farmasi & Klinis), 2024)
The outer skin of robusta coffee bean (Coffea canephora) was a processing waste containing phenolic compounds with antioxidant role. This activity is relevant when used in cosmetic preparations such as peel-off masks, which form a thin elastic layer on the facial surface and are easy to remove. One of the important ingredients of peel-off masks is plasticizer such as sorbitol characterized by flexibility, not easily fragile, and elasticity. Therefore, this research aimed to develop peel-off formula from robusta coffee skin by influencing sorbitol variations on the characteristics of masks in the form of gel. A total of six gel masks formulas were made with sorbitol variations of 10%, 12.5%, and 15%. The two types of gel base used were Carbopol 940 and HPMC (Hydroxy Propyl Methyl Cellulose), at concentrations of 0.25% and 4%, respectively. The results showed that sorbitol variations affected the physical characteristics (p > 0.05) but did not influence antioxidant activity of robusta coffee skin extract peel-off masks.